The Relationship between the Soluble Receptor for Advanced Glycation End Products and Oxidative Stress in Patients with Palmoplantar Warts - Cristina Iulia Mitran; Ilinca Nicolae; Mircea Tampa; Madalina Irina Mitran; Constantin Caruntu; Maria Isabela Sarbu; Corina Daniela Ene; Clara Matei; Antoniu Cringu Ionescu; Simona Roxana Georgescu; Mircea Ioan Popa (Medicina, 2019)
Background and objectives: Warts are the most common lesions caused by human papillomavirus (HPV). Recent research suggests that oxidative stress and inflammation are involved in the pathogenesis of HPV-related lesions. It has been shown that the soluble receptor for advanced glycation end products (sRAGE) may act as a protective factor against the deleterious effects of inflammation and oxidative stress, two interconnected processes. However, in HPV infection, the role of sRAGE, constitutively expressed in the skin, has not been investigated in previous studies. Materials and Methods: In order to analyze the role of sRAGE in warts, we investigated the link between sRAGE and the inflammatory response on one hand, and the relationship between sRAGE and the total oxidant/antioxidant status (TOS/TAS) on the other hand, in both patients with palmoplantar warts (n = 24) and healthy subjects as controls (n = 28). Results: Compared to the control group, our results showed that patients with warts had lower levels of sRAGE (1036.50 ± 207.60 pg/mL vs. 1215.32 ± 266.12 pg/mL, p < 0.05), higher serum levels of TOS (3.17 ± 0.27 vs. 2.93 ± 0.22 µmol H2O2 Eq/L, p < 0.01), lower serum levels of TAS (1.85 ± 0.12 vs. 2.03 ± 0.14 µmol Trolox Eq/L, p < 0.01) and minor variations of the inflammation parameters (high sensitivity-CRP, interleukin-6, fibrinogen, and erythrocyte sedimentation rate). Moreover, in patients with warts, sRAGE positively correlated with TAS (r = 0.43, p < 0.05), negatively correlated with TOS (r = −0.90, p < 0.01), and there was no significant correlation with inflammation parameters. There were no significant differences regarding the studied parameters between groups when we stratified the patients according to the number of the lesions and disease duration. Conclusions: Our results suggest that sRAGE acts as a negative regulator of oxidative stress and could represent a mediator involved in the development of warts. However, we consider that the level of sRAGE cannot be used as a biomarker for the severity of warts. To the best of our knowledge, this is the first study to demonstrate that sRAGE could be involved in HPV pathogenesis and represent a marker of oxidative stress in patients with warts.